Analysis of Physical Characteristics and Soil Degradation Due to Erosion and Rehabilitation Recommendation Based on GIS in Protected Forest Area of Mount Sirimau - Tupanno, Carla E; Talakua, Silwanus; Soplanit, Rudy; Osok, Rafael M (JURNAL BUDIDAYA PERTANIAN, 2023)
Forest areas are designated as protected forests if they function as a provider of clean water reserves, erosion control, city lungs or other functions. Disruption of forest land resources has an impact on changes in the physical properties of the soil and soil degradation due to erosion. Objectives of this study were: 1) to examine the relationship between soil physical properties, 2) to determine soil degradation due to erosion, 3) to examine the relationship between soil physical properties and the level of soil degradation due to erosion, 4) to determine recommendations for land rehabilitation. Research observations were made based on 15 sample areas representing 212 land units. All analyzes were carried out based on Geographic Information Systems (GIS). The physical properties of the soil studied included texture, structure, pore distribution, permeability, particle density and oven dry mass density; whereas soil degradation analysis was based on RUSLE: A=RKLSCP (Renard et al., 1997), and correction of the erosion model A=0.2547RKLSCP (Talakua S.M. and Osok, 2017. The rehabilitation recommendations analyzed were erosion tolerance, potential erosion and CP-maximum. Study results were: 1) The correlation between physical properties was significant (P-value = 0.000*-0.018*) with a positive correlation coefficient (0.163-0.999) and negative one (0.199-0.998); 2) The average erosion rate was: light 3.60 t/ha/year (1425.20 ha), moderate 32.03 t/ha/year (410.28 ha), heavy 108.95 t/ha/year (946 .2 ha), very heavy 426.83 t/ha/year (457.44 ha); 3) There was a significant correlation between the physical properties of the soil and the amount of erosion with a P-value = 0.000*–0.029* with a positive (0.152-0.161) and a negative (0.150-0.151) correlations; 4) Recommendation for rehabilitation are agroforestry patterns combined with tillage and planting of plants according to contour lines on slopes of 0–8%, planting grass in strips, planting low ground cover on high density plantation crops and maintaining secondary and primary forests.